170k views
1 vote
6x - 9= y y= -3x using the system of linear equation by substitution Help please! This is due really soon

User Janani
by
4.6k points

1 Answer

7 votes

Answer:

x = 1 and Y = -3

Explanation:

Rewrite equations:

y=−3x;6x−9=y

Step: Solvey=−3xfor y:

y=−3x

Step: Substitute−3xforyin6x−9=y:

6x−9=y

6x−9=−3x

6x−9+3x=−3x+3x(Add 3x to both sides)

9x−9=0

9x−9+9=0+9(Add 9 to both sides)

9x=9

9x

9

=

9

9

(Divide both sides by 9)

x=1

Step: Substitute1forxiny=−3x:

y=−3x

y=(−3)(1)

y=−3(Simplify both sides of the equation)

Answer:

x=1 and y=−3

User Dxc
by
4.9k points